Taxonomic and functional adaption of the gastrointestinal microbiome of goats kept at high altitude (4800 m) under intensive or extensive rearing conditions. Issue 3 (19th January 2021) - Zhang, Ke; He, Chong; Xu, Yangbin; Zhang, Chenguang; Li, Chao; Jing, Xu; Wang, Meili; Yang, Yuxin; Suo, Langda; Kalds, Peter; Song, Jiuzhou; Wang, Xiaolong; et al.
ABSTRACT: The gut microbiota composition is influenced by the diet as well as the environment in both wild and domestic animals. We studied the effects of two feeding systems on the rumen and hindgut microbiome of semi-feral Tibetan goats kept at high altitude (∼4800 m) using 16S rRNA gene and metagenomic sequencing. Intensive drylot feeding resulted in significantly higher zootechnical performance, narrower ruminal acetate: propionate ratios and a drop in the average rumen pH at slaughter to ∼5.04. Hindgut microbial adaption appeared to be more diverse in the drylot group suggesting a higher influx of undegraded complex non-starch polysaccharides from the rumen. Despite their higher fiber levels in the diet, grazing goats exhibited lower counts of Methanobrevibacter and genes associated with the hydrogenotrophic methanogenesis pathway, presumably reflecting the scarce dietary conditions (low energy density) when rearing goats on pasture from extreme alpine environments. These conditions appeared to promote a relevant abundance of bacitracin genes. In parallel, we recognized a significant increase in the abundance of antibiotic resistance genes in the digestive tracts of drylot animals. In summary, this study provides a deeper insight into the metataxonomic and functional adaption of the gastrointestinal microbiome of goats subject to intensive drylot and extensive pasture rearing conditions at high altitude. Abstract : Composition and functional potential of gut microbiome of semi-feral Tibetan goats differs in drylot versus free-range grazing feeding systems.